Evaluation of physio-chemical properties of saliva and comparison of its relation with dental caries - Subha Dogra; Deepak Bhayya; Ruchi Arora; Deepesh Singh; Dashmesh Thakur (Wolters Kluwer Medknow Publications, 2013)
Objective: Objective was to evaluate the relationship between physio-chemical properties of saliva such as flow rate, buffering capacity, pH, Streptococcus mutans in saliva and its relationship with dental caries. Study design: Eighty children were evaluated for physio-chemical properties of saliva, out which 40 were caries-active (group 1) and 40 caries-free (control group). Caries status of each child was scored by using DMFS and dfs indices to get a combined DMFS and dfs score. The physio-chemical properties were evaluated using Saliva Check (GC Asia Dental Pte Ltd- India) and streptococcus mutans using Dentocult SM Strip Mutans. Result: Flow rate, pH, and buffering capacity of saliva in caries-active children were decreased but not statistically significant. The Streptococcus mutant count of saliva was increased significantly in caries-active children. Conclusion: The physio-chemical properties of saliva like pH, buffering capacity, salivary flow rate, concentration of various components like proteins, calcium and antioxidant defense system play a major role in the development of caries. Hence, more clinical and laboratory studies are needed to determine the exact relationship between these physio-chemical properties of saliva and dental caries.